2007
DOI: 10.1111/j.1464-5491.2007.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction, ambulatory pulse pressure and albuminuria are associated in Type 2 diabetic subjects

Abstract: Increased PP is associated with endothelial activation and albuminuria in Type 2 diabetic patients. Thus, endothelial dysfunction may represent a pathophysiological link between an elevated PP and microvascular complications in these subjects. Prospective studies are needed to further elucidate these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…First, what are the underlying pathophysiological mechanisms connecting the haemodynamic abnormalities, elevated PP and blunted nocturnal BP decline, with the development of microvascular complications, in casu progression of nephropathy in type 2 diabetes? We have previously demonstrated strong associations between endothelial perturbation and both non-dipping [17] and elevated PP [5], suggesting that an enhanced level of endothelial cell activation could represent a link between these haemodynamic abnormalities and the development of microvascular complications in type 2 diabetes, possibly by promoting inflammation and atherosclerosis and by increasing the tendency of blood clotting. However, we were unable to make firm conclusions regarding causality due to the cross-sectional design of the studies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…First, what are the underlying pathophysiological mechanisms connecting the haemodynamic abnormalities, elevated PP and blunted nocturnal BP decline, with the development of microvascular complications, in casu progression of nephropathy in type 2 diabetes? We have previously demonstrated strong associations between endothelial perturbation and both non-dipping [17] and elevated PP [5], suggesting that an enhanced level of endothelial cell activation could represent a link between these haemodynamic abnormalities and the development of microvascular complications in type 2 diabetes, possibly by promoting inflammation and atherosclerosis and by increasing the tendency of blood clotting. However, we were unable to make firm conclusions regarding causality due to the cross-sectional design of the studies.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous previous studies have established the superiority of 24 h AMBP over conventional office BP measurement for the association with [1,5,15,32,33] and prediction of hypertensive end-organ damage in diabetes [9,34,35]. Moran et al found that office and 24 h systolic AMBP were independently associated with albuminuria in elderly type 2 diabetic patients [4]; however in the longitudinal study mentioned above [9], ambulatory PP predicted progression of albuminuria above and beyond office BP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…14 Increased UAE has also been associated with proinflammatory markers [14][15][16] and arterial stiffness [17][18][19][20] in older adults and in adults with cardiovascular disease and diabetes. The clinical data demonstrate a consistent significant association of increases in UAE with progression in cardiovascular and renal injury.…”
Section: Introductionmentioning
confidence: 99%